Dynamics and stability of ethylene polymerization in multizone circulating reactors - Ghasem, N.M.; Ang, W.L.; Hussain, Mohd Azlan (Korean Journal of Chemical Engineering, 2009)
Multizone circulating bed reactors (MZCR) have the exclusive characteristics of producing polymers of different molecular weights in a single particle. Traditional fluidized bed reactors, on the other hand, can produce only one kind of molecular weight with relatively narrow distribution. A dynamic model for the MZCR is used to illustrate the basic dynamic behavior of the new reactor design used for polyethylene production. The model is used to study the copolymerization of ethylene with butene. Several parameter sensitivity analyses are performed to show the computer-simulated time responses for reactor temperature, number-average molecular weight, weight-average molecular weight, catalyst feed rate and the monomer/comonomer concentration along the reactor length. At certain operating conditions dynamic instability is observed and the results for the effect of cooling water temperature, catalyst feed rate, monomer and comonomer initial feed concentration on the reactor temperature and polymer molecular weight reveal that the system is very sensitive to disturbances in the heat exchanger coolant temperature. Also, at some operating conditions, the reactor temperature oscillates above the polymer melting temperature. Temperature runaway above polymer softening point is a serious problem which may cause polymer melting and hence reactor shutdown. The oscillatory behavior of the reactor temperature necessitates a suitable temperature control scheme to be installed.